TREE SPECIES DENSITY AND DIVERSITY IN JEMAA LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Zankan, J. A. A.; Endas, L.; Abubakar, Y. M.; Yakubu, I. B. (FUDMA JOURNAL OF SCIENCES, 2023)
Vegetation is one of the living components of the environment that provides food for man and shelter for wildlife. This paper assesses tree species density and diversity in Jema’a Local Government, Kaduna State, Nigeria with a view to providing information for sustainable natural resource management. Stratified sampling design was used to group the study area into four land use types, namely: forests, woodlands, farmlands and built-up Areas. Data for this study were collected from 48 sample plots of 20 × 20m laid out systematically across the study land use types. The establishment of plots was done by the use of measuring tape, ranging poles and GPS. Within each plot, tree species density and diversity, height, and dbh were obtained. Descriptive statistics was used to analyze the data. Result indicates that a total of 556 individual stands of woody species were identified and enumerated in the study area through the field survey. These belong to 50 species, 48 genera and 26 families. Species which recorded the highest representation are Sterculia setigera (10.6%), Terminalia macroptera (8.55%), Anona senegalensis and Lophira alata had (7.82%) each. While, the families combretaceae and fabaceae had the highest number of tree species of five each. It is recommended that a sustainable forest management be urgently adopted that involves indigenous people participation and the government
Keywords: Conservation, Management, Tree Species Density and Diversity